2006
DOI: 10.1586/14737140.6.9.1281
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapy of breast cancer: maximizing control, minimizing morbidity

Abstract: The goal of locoregional therapy in breast cancer has remained unchanged for a century: the eradication of all malignant cells from the breast and draining lymph nodes, hopefully prior to them having spread to distant organs. However, how we accomplish this goal has changed dramatically over this time period and our success in achieving this goal has been greatly enhanced by improvements in breast imaging and systemic therapies. The therapeutic importance of surgery and radiation has been underestimated in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 204 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The tracer entrapment within tumor core during and after the thaw process as seen in the VX2 study suggests the use of Freezethaw assisted injection of active drug not only during the resection but also in the resection cavity margins. The local injection of cytotoxic would help priming residual tumor cells to adjuvant systemic therapies 49,50 , and/or radiotherapy 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracer entrapment within tumor core during and after the thaw process as seen in the VX2 study suggests the use of Freezethaw assisted injection of active drug not only during the resection but also in the resection cavity margins. The local injection of cytotoxic would help priming residual tumor cells to adjuvant systemic therapies 49,50 , and/or radiotherapy 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Margin assessment, sentinel lymph node mapping and biopsy (SLNB), resection cavity shaving (RCS), partial breast irradiation (PBI), or photodynamic therapy (PDT) is common procedure 4,5 . During breast conserving surgery (BCS), most local recurrences in the conserved breast appear close to the tumorectomy cavity [6][7][8] ; pathologic studies of mastectomy specimens have shown that tumor cells rarely extend 4 cm beyond the index lesion 8 . These clinicopathological facts have spurred the development of techniques that target the tumor bed 9 , such as routine circumferential resection cavity shaving 5 or partial breast irradiation (PBI).…”
Section: Introductionmentioning
confidence: 99%
“…Regional lymphadenectomy in addition to primary tumor excision has been incorporated into the routine treatment of many malignancies [1,2,3]. In genitourinary surgery this is clearly seen in the management of testis and penile cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of local recurrence in the management of breast cancer, and its potential impact on survival, is increasingly clear [15][16][17]. But the present limitations or concerns regarding cryoablation do not argue against further evaluation, but rather the importance of well-designed clinical trials to optimize patient selection and identify patients who may not have had a complete response.…”
mentioning
confidence: 99%